An elastic element in the protocadherin-15 tip link of the inner ear - Raul Araya-Secchi (Nature Portfolio, 2016)
Tip-link filaments convey force to activate hair cells, important sensory receptors. Here the authors solve a partial structure of human protocadherin-15, a tip-link component with an unusual Ca2+–free linker that bends and is predicted to confer flexibility to this filament during inner-ear mechanotransduction.